(untitled) (Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the effect of competence and compensation on employee performance with work motivation as a mediating variable at the Environmental Service Office of Mojokerto City. The research method used is quantitative with an explanatory approach. Data was collected through a survey using questionnaires completed by 81 employees as respondents. The analysis technique used is path analysis with the help of SPSS 22. The results show that competence has a significant effect on employee performance (β = 0.410; p < 0.001) and a significant effect on work motivation (β = 0.407; p < 0.001). Work motivation also significantly affects employee performance (β = 0.271; p = 0.008). Meanwhile, compensation does not have a direct effect on employee performance (β = 0.116; p = 0.215) but has an indirect effect through work motivation (β = 0.145; p = 0.166). Path analysis shows that competence has a total effect of 0.577 on employee performance, while compensation has a total effect of 0.133. The implications of this study indicate that increasing employee competence can enhance motivation and performance, while the compensation system needs to be adjusted to be more effective in improving employee productivity.